Scoping review of head and neck neoplasms presenting with obstructive sleep apnoea: the importance of flexible nasendoscopy. Issue 1 (24th June 2020) - Moore, Phillip; Cardemil, Felipe; Hayward, Nathan J.; Flatman, Samuel
Abstract: Background: Obstructive sleep apnoea (OSA) can be caused by neoplasms involving the upper aerodigestive tract. Currently, many of these patients have this diagnosis missed, as most adults diagnosed with OSA do not undergo adequate head and neck examination including flexible nasendoscopy. We performed a review of the literature to shed light on this phenomenon and outline the pathologies and issues surrounding this sub‐population of patients diagnosed with OSA. Methods: A scoping review of the literature was conducted on head and neck neoplasms presenting with OSA. Data were extracted on demographics, clinical presentation, histopathology, treatment and patient outcomes. Results: Sixty‐seven articles were included, describing 79 patients. Mean age was 45.8 years, and 77.2% were male. Symptoms of OSA were present for an average of 29.2 months before a diagnosis of causative neoplasm was made. Forty‐two different benign and malignant histopathological entities were reported. At diagnosis, the causative pathology of 100% of patients was visible on head and neck examination including flexible nasendoscopy, while only 53.2% were visible on trans‐oral examination. One‐third of patients had commenced inappropriate treatment for OSA, including three who had undergone sleep surgical procedures. The majority of patients were treated with surgery alone (72.2%). Conclusion: Although rare, neoplasms of the upper aerodigestive tract should be considered as a cause of OSA, especially in patients experiencing other symptoms in addition to the typical symptoms of OSA. They should particularly be considered in patients with comparatively lower body mass index or those with worsening OSA without an apparent cause identified. Abstract : A scoping review of the literature of patients with head and neck neoplasms presenting with obstructive sleep apnoea. This review highlights the importance of thorough head and neck examination, including flexible nasendoscopy, in the assessment of adult patients presenting with obstructive sleep apnoea.